Balance control in elite polish acrobats - Juras, G.; Slomka, K.; Raczek, J.; Blaszczyk, J. W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Performance of some motor tasks, especially in professional sport, requires a perfect interaction between the sensory and motor systems. There is a very common conviction that experts in acrobatics, gymnastics or dancing have a great sense of balance. The objectives of this research project were (1) to establish the effect of expertise in acrobatics on postural control and (2) determination of the role played by visual system in different postural tasks. Methods The research experiment was conducted on 12 highly trained acrobats aged 22,1±1,9 and 25 students aged 21,4±1,1 (control group). The subjects were examined using a force platform and a stabilometer. The sway on the force platform (Kistler) was described by standard quantifying the change of the COFP (center-of-foot pressure) position using BioWareTM software. A maximal leaning test (forward, backward and to the right/left side) was also performed to determine ranges of postural stability [1]. Characteristics of the COFP (mm) average displacements range from normal stance to maximal leaning position were used to evaluate quality of the balance control. Also the dynamic balance was measured on a movable platform of a stabilometer. Two parameters were calculated to characterize the dynamic balancing performance: instability (integral of average module of inclination) (degree/s) and balance control (number of corrections). Balance tasks were performed in sagittal and frontal plane. All tests were carried out with and without visual control. Results The achieved empirical data and its analysis allowed to conclude that acrobats have significantly better balance control then students. Nevertheless very few differences were not statistically significant. Sports experts were better then students performing more complex tasks (p<0,001) and tasks with lack of vision (p<0,01). Interestingly, the level of equilibrium of movements in all subjects was better in a frontal axis and determined by visual information in all measurements. It was surprising that during quiet stance both acrobats and students obtained better results with a lack of vision yet these differences were not significant. The role of vision increased when the demands of balance control increased (more complex balance task). In addition, the influence of visual control during these tasks was more significant in case of measurements carried out in the frontal plane. As far as the main goal of that paper is concerned results obtained from the force platform and the stabilometer do not correlate in acrobats. Discussion /Conclusions 1. Some common mechanism determining balancing behavior exists. 2. Practicing acrobatics contributes to the development of specific postural control strategies. 3. Different methods for evaluating the balance control should be treated as complementary and/or independent in highly-qualified sportsmen.